Impact of a Data-driven Teaching Approach on 9th Graders Conceptual Understanding of Machine Learning - Marx, Erik; Leonhardt, Thiemo; Bergner, Nadine (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
This study aimed to investigate the impact of a data-driven teaching approach on students’ conceptual understanding of machine learning (ML). To this end, an exemplary intervention was designed and evaluated using a pre- and post-test design and a German-language Concept Inventory on Machine Learning. A total of 83 German ninth-grade students participated in the study. The results revealed significant learning gains related to data handling and the ML workflow. In contrast, conceptions about the inner workings of ML models largely persisted. The effectiveness of the intervention varied depending on context, with greater gains observed in the text generation domain than in facial recognition, highlighting challenges in cross-contextual transfer of understanding. A regression analysis showed no significant influence of students’ pre-instructional conceptions on learning outcomes. These findings demonstrate both the potential and the limitations of data-driven teaching approaches and emphasize the need for more explicit engagement with learners’ misconceptions to foster deeper conceptual change.